Penerapan Teknoligi Informasi Berbasis WEB (Electronic Gpvernment) Dalam Rangka Memberikan Layanan Informasi Punlik - Idris, Khalid (Jurnal Administrasi Publik, 2013)
Abstract: Implementation of Web-based Information Technology (electronic Government) in Conveying Public Information Service. This study was based on the emergence of less satisfying and less effective manual service. To achieve effective service, we should impose an electronic government. Focus of this study would be implementation of electronic government in the city of Malang, supporting and hindering factors in implementation of electronic government, also efforts of kominfo agency in improving information service quality. Study result showed that implementation of electronic government in the city of Malang is quite effective, this can be seen from lots of visitor/people who visit official site of Malang, and existence in interaction between people (user) with official apparatus shown in complaint column. Suggestion from this study would be that official site of Malang should be made more interesting in order to attract more people to visit the official site of Malang. Keywords: information technology, electronic government, public service Abstrak: Penerapan Teknologi Informasi Berbasis Web (electronic Government) Dalam Rangka Memberikan Layanan Informasi Publik. Penelitian ini didasarkan pada munculnya pelayanan manual yang kurang memuaskan dan kiurang efektif. Untuk mencapai hal yang efektif maka perlu diadakannya electronic government. Fokus penelitian ini adalah penerapan electronic government pada kota Malang, Faktor pendukung dan penghambat penerapan electronic government, serta upaya dinas kominfo dalam meningkatkan kualitas layanan informasi. Hasil penelitian ini menunjukkan bahwa penerapan electronic government di kota Malang sudah cukup efektif, hal ini dapat dilihat dari banyaknya pengunjung / masyarakat yang mengunjungi situs resmi pemerintah kota Malang, serta adanya interaksi antara masyarakat (user) dengan aparatur pemerintah yang tertuang dalam kolom pengaduan. Saran penelitian ini adalah hendaknya situs resmi pemerintah kota Malang dibuat lebih menarik agar membuat masyarakat merasa lebih tertarik untuk membuka situs resmi pemerintah kota Malang. Â  Kata kunci: teknologi informasi, electronic government, pelayanan publik